2019
DOI: 10.31258/ijesh.1.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Gaining competitive advantage through new product development capability in Malaysian Government Linked Companies

Abstract: A new product development capability can be shown through organisational routines that shape the processes of innovation, which are aimed to reconfigure a firm’s product portfolio. It is aimed to create a concrete physical asset from an idea and this relates to the innovation that is the mechanism by which firms to produce new products, processes and systems that essential in order to adapt market changes, technologies and types of competition. New product development capability aids corporate managers plan an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It is aimed at creating concrete physical assets from an idea, and it relates to innovation i.e. the mechanism by which companies produce new products, processes and systems which are important to adapt to changes in market, technology, and types of competition (Abdullah, 2019). Khattab (2017) found that there was a significant impact between PDC, technical capabilities, research, and human resource capabilities on product innovation, supply chain innovation and organizational innovation.…”
Section: Relationship Between Pdp and Rpamentioning
confidence: 99%
See 1 more Smart Citation
“…It is aimed at creating concrete physical assets from an idea, and it relates to innovation i.e. the mechanism by which companies produce new products, processes and systems which are important to adapt to changes in market, technology, and types of competition (Abdullah, 2019). Khattab (2017) found that there was a significant impact between PDC, technical capabilities, research, and human resource capabilities on product innovation, supply chain innovation and organizational innovation.…”
Section: Relationship Between Pdp and Rpamentioning
confidence: 99%
“…PCC is the company's capability to dynamically configure products with visibility of product origin, products that are different from competitors, and products that are difficult to imitate so that the products produced by the company are more efficient in terms of cost and quality (Hanfan, 2021). PCC helps company managers plan and execute strategies successfully while securing a sustainable competitive advantage (Abdullah, 2019). Hosseini et al (2018) found PCC was influenced by competitive advantage factors, namely quality, efficiency, innovation, and accountability.…”
Section: Relationship Between Pcc and Rpamentioning
confidence: 99%
“…After conducting a mixed-method approach, we identified these capabilities as MR, CI, SCM, CRM and NPD capabilities. Some previous studies consider the relationship between CA and each of these capabilities independently (Abdullah, 2019;Abeysekara et al, 2019;Bhat and Darzi, 2016;Helm et al, 2020;Nadeau and Casselman, 2008;Soltani et al, 2014;Somiah et al, 2020;Thatte et al, 2013;Vazirzanjani and Hooshmand, 2016). KBM can integrate these marketing capabilities to create CA.…”
Section: Knowledge-based Marketing and Competitive Advantagementioning
confidence: 99%
“…MSMEs that successfully develop new products can increase their competitiveness and business growth in an increasingly competitive market. New product development (NPD) is a process that involves creating, designing, and bringing new products to market (Abdullah, 2019). In addition, NPD can also help MSMEs to increase the added value of the products or services they offer.…”
Section: Introductionmentioning
confidence: 99%